Parkinson’s disease and awareness of the passage of time: Perceived health, emotion, and self-transcendence - Florie Monier; Sylvie Droit-Volet; Michael Dambrun; Sophie Monceau; Laure Delaby; Isabelle Rieu; Tiphaine Vidal; Franck Durif; Ana Marques (PLoS ONE, 2026)
This study examined passage-of-time judgments in patients with Parkinson’s disease, compared to age-matched healthy controls. The aim was to determine whether these temporal judgments are influenced by affects or by psychological representations of the self, which may differ between these populations. The self has indeed been identified as a potential factor shaping time cognition, either through the minimal self, rooted in emotional and bodily sensations, or through cognitive self-representations. We used self-reported scales to measure participants’ passage-of-time judgments across two distinct dimensions: (1) for distant life periods (e.g., now compared to 5 years ago), and (2) for shorter and more recent time periods (e.g., day, week). Participants also completed questionnaires assessing emotional states (e.g., perceived health, well-being, happiness). To more specifically explore self-representation, we measured levels of self-transcendence, defined as the pursuit of meaning that extends beyond oneself and one’s own needs or interests, to examine whether individuals viewed themselves in a self-centered way or held a more open and interconnected sense of self. The results did not show that Parkinson’s disease alter passage-of-time judgments, whether related to recent or distant past periods. However, the findings confirmed that judgments about the distant past and recent experiences reflect two distinct forms of temporal judgment. The former was associated with self-consciousness and the projection of the self across the lifespan, whereas the latter is more closely linked to emotional and bodily state representations, shaped by perceived health, emotional condition, and overall well-being.